Unusually large tsunamis frequent a currently creeping part of the Aleutian megathrust - Witter, Robert C.; Carver, Gary A.; Briggs, Richard W.; Gelfenbaum, Guy; Koehler, Richard D.; La Selle, SeanPaul; Bender, Adrian M.; Engelhart, Simon E.; Hemphill-Haley, Eileen; Hill, Troy D. (Geophysical Research Letters, 2016)
Current models used to assess earthquake and tsunami hazards are inadequate where creep dominates a subduction megathrust. Here we report geological evidence for large tsunamis, occurring on average every 300–340 years, near the source areas of the 1946 and 1957 Aleutian tsunamis. These areas bookend a postulated seismic gap over 200 km long where modern geodetic measurements indicate that the megathrust is currently creeping. At Sedanka Island, evidence for large tsunamis includes six sand sheets that blanket a lowland facing the Pacific Ocean, rise to 15 m above mean sea level, contain marine diatoms, cap terraces, adjoin evidence for scour, and date from the past 1700 years. The youngest sheet and modern drift logs found as far as 800 m inland and >18 m elevation likely record the 1957 tsunami. Previously unrecognized tsunami sources coexist with a presently creeping megathrust along this part of the Aleutian Subduction Zone.